The evaluation in reports of trainees of the course of license in letters: portuguese language - of UFPA (Revista Internacional de Formação de Professores, 2019)
Announcing the current tendency to consider assessment as a means of reorienting the teaching-learning system, Mere Abramowicz (1998) drew attention, at the end of the twentieth century, to the relation between evaluation and the existential condition of the teacher, which, according to the author, must be an active subject of the process of evaluating one's performance (1998, 40). Thus, today, evaluation is understood not only as a way of measuring students' learning. It is believed that his results signal, to the teacher, the extent to which the teaching strategies selected by him are effective. According to Luckesi (2002), to avoid authoritarianism and conservatism, the evaluation must be diagnostic and innovative, allowing the identification of strategies to be used (2002, 43). This work aims to verify, through the analysis of reports submitted by trainees of the Licenciatura Course in Portuguese Language - Federal University of Pará, if their evaluation proposal reflects this conception of evaluation, that is, if future mother tongue teachers propose, in fact, a learning evaluation model different from the traditional and technicist, which aims only at the assignment of grades and the classification of students in basic education.
Keywords: Teacher training. Experience. Internship.